On Soft Semi-Open Sets and Soft Semi-Continuity in Fuzzifying Soft Topological Spaces - Ramadhan A. Mohammed; Tahir H. Ismail; A. A. Allam (Eurasian Journal of Science and Engineering, 2018)
In this paper, a new class of soft open sets in fuzzifying soft topological spaces called soft semi open sets is introduced and its fuzzifying soft topological properties is studied and investigated. Moreover, we aim to introduce and study the concepts of soft semi neighborhood system, soft semi interior, soft semi closure and soft semi boundary operators, in fuzzifying soft topological spaces. Finally, the concept of soft semi-continuity is defined and studied.